PENGARUH KEMAMPUAN KERJA DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI PT. BANGTELINDO - Adella Nanda Ernanto; Kustini Kustini (STKIP Persada Khatulistiwa Sintang, 2022)
The development of an organization depends on the presence of human resources owned. Therefore, human resources are important assets to be developed efficiently and effectively because they can create good and optimal performance. In order to achieve meaning for the organization, industry is of course required to be able to create conditions or situations that can allow and encourage workers to develop skills and abilities optimally. The purpose of carrying out the research is to analyze: 1) Influence work ability on performance employees at PT. Bangtelindo; 2) The influence of the workload on performance employees at PT. Bangtelindo. The research method that the researcher uses is a quantitative method. The use of the population includes technician employees many as 95 people, with a sample of 49 respondents. The technique for taking a sample is by means of Simple Random Sampling. The technique in the analysis the researcher uses is the analysis with Partial Least Square. Based on the results of the study, researchers have carried out showing findings in the form of: (1) Workability has a contribution to the performance of employees; (2) Workload has a contribution to the performance of employees